User behaviour and hoax information on social media case of Indonesia - Erwan Effendi (Faculty of Communications Science, Dr. Soetomo University, 2023)
The present study examines the influence of user behaviour on the propagation of deceptive information on social media platforms within the Indonesian setting. It specifically focuses on the ramifications of such behaviour on political, health, business competition, and environmental matters. The beginning of the study highlights the gravity of the dissemination of hoaxes on social media platforms, attributing it to the algorithms that prioritise information that is engaging, frequently characterised by provocative or sensationalised headlines. The methodology section discusses how we adopted a mixed-methods approach to examine both quantitative data from social media metrics and qualitative data from user interviews. Additionally, network analysis was used to identify disinformation dissemination across platforms. The findings suggest that hoaxes spread quickly because they grab users' attention better than real information. Our research also shows that these fraudulent schemes can increase social strife, anger, and prejudice against certain groups or people, tarnishing their social standing. Our research shows that in democratic nations like Indonesia, where freedom of expression is important, incorrect information is often used for electoral gain. Our analysis shows that users need better digital literacy to handle this issue. Training people to spot fake news is one way to combat the growing problem of disinformation.